Successful management of a patient with severe brady-arrhythmia in peripartum period - Tandon, Aditi; Satia, Meena; Badhwar, Vijaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Pregnancy is a normal physiological state with hyperdynamic circulation that is characterised by important physiological changes, many of which take place in the cardiovascular system. Few patients with physiological bradycardia may, in the second trimester, feel symptomatic as their blood pressure drops due to a reduction in systemic vascular resistance however, treatment is rarely required. Pathological bradycardia in pregnant women is rare and usually secondary to either Congenital heart block, Myocarditis, or Severe Hypocalcaemia with an incidence as low as 1:20 000 women. Authors present a rare case of severe bradycardia during peripartum period who required LSCS in view of IUGR with Anhydroamnios. On admission her general condition was good her pulse was 42 beats per mins and BP was 170/100 mm of Hg with 1+ protinuria. A clinical impression of preeclampsia was made. ECG showed sinus bradycardia with no irregularity. 2 DEcho showed no structural lesion in the heart and normal functional capacity so dilated peripartum cardiomyopathy was ruled out. Her serum electrolytes were normal and serum calcium and magnesium was markedly reduced which was corrected. Post operatively on day 4 pulse was mor than 60 and she was transferred out of ICU. The ECG performed on day 6 was normal.